2022
DOI: 10.1002/jcv2.12094
|View full text |Cite
|
Sign up to set email alerts
|

Early neurodevelopmental problems and risk for avoidant/restrictive food intake disorder (ARFID) in 4‐7‐year‐old children: A Japanese birth cohort study

Abstract: Background: An overrepresentation of neurodevelopmental problems (NDPs) has been observed in individuals with avoidant/restrictive food intake disorder (ARFID).Previous studies on the association between ARFID and NDPs have been limited by cross-sectional data from clinical samples of small size. This study aimed to extend previous research by using prospectively collected data in a non-clinical child cohort.We examined the occurrence of early NDPs in 4-7-year-old children with suspected ARFID and how predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
(58 reference statements)
2
19
2
Order By: Relevance
“…The majority were conducted in Western countries ( n = 23) (Bertrand et al., 2021; Cooney et al., 2018; Eddy et al., 2015; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Goldberg et al., 2020; Gonçalves et al., 2019; Katzman et al., 2021; Koomar et al., 2021; Krom et al., 2019; Kurz et al., 2015; Murray et al., 2022; Nicely et al., 2014; Norris et al., 2014; Nygren et al., 2021; Ornstein et al., 2013; Pinhas et al., 2017; Schmidt et al., 2018; Schöffel et al., 2021; Venema et al., 2022; Williams et al., 2015), predominantly the USA ( n = 9) (Eddy et al., 2015; Fisher et al., 2014, 2015; Forman et al., 2014; Koomar et al., 2021; Murray et al., 2022; Nicely et al., 2014; Ornstein et al., 2013; Williams et al., 2015), with two carried out in multiple countries (Fisher et al., 2014; Pinhas et al., 2017). One study took place in the Middle East (Iron‐Segev et al., 2022) and six in East Asian countries: four in Japan (Dinkler et al., 2022a, 2022b; Seike et al., 2016a, 2016b), one in Taiwan (Chen et al., 2020) and one in Singapore (Wong et al., 2022). The majority ( n = 21) of studies focussed on clinical populations (Bertrand et al., 2021; Cooney et al., 2018; Eddy et al., 2015; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Goldberg et al., 2020; Katzman et al., 2021; Koomar et al., 2021; Krom et al., 2019; Murray et al., 2022; Nicely et al., …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority were conducted in Western countries ( n = 23) (Bertrand et al., 2021; Cooney et al., 2018; Eddy et al., 2015; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Goldberg et al., 2020; Gonçalves et al., 2019; Katzman et al., 2021; Koomar et al., 2021; Krom et al., 2019; Kurz et al., 2015; Murray et al., 2022; Nicely et al., 2014; Norris et al., 2014; Nygren et al., 2021; Ornstein et al., 2013; Pinhas et al., 2017; Schmidt et al., 2018; Schöffel et al., 2021; Venema et al., 2022; Williams et al., 2015), predominantly the USA ( n = 9) (Eddy et al., 2015; Fisher et al., 2014, 2015; Forman et al., 2014; Koomar et al., 2021; Murray et al., 2022; Nicely et al., 2014; Ornstein et al., 2013; Williams et al., 2015), with two carried out in multiple countries (Fisher et al., 2014; Pinhas et al., 2017). One study took place in the Middle East (Iron‐Segev et al., 2022) and six in East Asian countries: four in Japan (Dinkler et al., 2022a, 2022b; Seike et al., 2016a, 2016b), one in Taiwan (Chen et al., 2020) and one in Singapore (Wong et al., 2022). The majority ( n = 21) of studies focussed on clinical populations (Bertrand et al., 2021; Cooney et al., 2018; Eddy et al., 2015; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Goldberg et al., 2020; Katzman et al., 2021; Koomar et al., 2021; Krom et al., 2019; Murray et al., 2022; Nicely et al., …”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the Canadian national surveillance study of ARFID with patients aged 5–18 years found the highest incidence in the 10–14 years old group (3.43 per 100,000 patients) (Katzman et al., 2021 ). The average age of patients with ARFID in the included studies ranged from 1.85 to 16.3 years (Cooney et al., 2018 ; Dinkler et al., 2022a , 2022b ; Eddy et al., 2015 ; Farag et al., 2022 ; Fisher et al., 2014 , 2015 ; Forman et al., 2014 ; Goldberg et al., 2020 ; Katzman et al., 2021 ; Krom et al., 2019 ; Murray et al., 2022 ; Nicely et al., 2014 ; Norris et al., 2014 ; Nygren et al., 2021 ; Pinhas et al., 2017 ; Schöffel et al., 2021 ; Venema et al., 2022 ; Wong et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations